LANGUAGE SHIFT BY THE JAVANESE IN PULO LOIH VILLAGE, PIDIE - Zulfikar Zulfikar; Zulfadli A. Aziz; Kismullah Abdul Muthalib (English Education Journal, 2020)
This research dissects the shift of Javanese into Acehnese in Pulo Loih village, Pidie. The Javanese live in the Pulo Loih village they followed the transmigration program which was not extended by the government and then moved to Pulo Loih village. This community is the focus of the researchers to conduct research that includes factors shifting Javanese into Acehnese and patterns of language shifting. Qualitative descriptive is a method applied in this study to collect data from 12 participants (eight adults and four children). After analyzing it, it was revealed that Javanese language users have disappeared among children while parents still interact with Javanese. There two factors that the researchers found in this study, namely internal factors and external factors. As for internal factors, parents do not teach Javanese and never interact in Javanese with their children. External factors include safety factors, economic factors, and social factors. These factors have proven that the Javanese language shift into the Acehnese language happened in Pulo Loih village, Pidie. There were four patterns of language shift when interacting, namely monolingual, subordinate bilingual, equal bilingual, and monolingual interaction patterns. Three patterns of language shift occurred in Javanese parents in the first generation who arrived in Pulo Loih village. The pattern is monolingual, subordinate bilingual, and equal bilingual. In the third generation, Javanese children, they have lost the fourth patterns, and the patterns of language shift directly to the fifth language shift pattern is monolingual.